Industry engagement: Accelerating discovery, application, and adoption through industry partnerships. (8th February 2022) - Peralta, Piarella; Hall, Megan P.; Singh Bhan, Seema; Brown, Kim; Parton, Marcus A.; Yeshwant, Krishna; Finucane, Stephanie; Keeling, Peter; Ofman, Joshua J.
Abstract : To advance the field of early detection with blood‐based screening tests and for industry to be able to significantly contribute to progress, collaboration, transparency, and innovative health economic approaches are needed. To achieve this, gaps in the current versus ideal frameworks need to be addressed at the regulatory, reimbursement, and guidelines levels by adopting an integrative, system‐level thinking to bring these important technologies to market and to improve on cancer outcomes by finding more cancers at earlier stages.